Omnidirectional Free-viewpoint Rendering Using a Deformable 3-D Mesh Model - Sato, Tomokazu; Koshizawa, Hiroyuki; Yokoya, Naokazu (International Journal of Virtual Reality, 2010)
This paper proposes a method to render free viewpoint images from omnidirectional videos using a deformable 3-D mesh model. In the proposed method, a 3-D mesh is placed in front of a virtual viewpoint and deformed by using the pre-estimated omnidirectional depth maps that are selected on the basis of position and posture of the virtual viewpoint. Although our approach is fundamentally based on the model-based rendering approach that renders a geometrically correct virtualized world, in order to avoid the hole problem, we newly employ a viewpoint-dependent deformable 3-D model instead of the use of a unified 3-D model that is generally used in the model based rendering approach. In experiments, free-viewpoint images are generated from the omnidirectional video captured by an omnidirectional multi camera system to show the feasibility of the proposed method for walk-through applications in the virtualized environment.